Comonomer Effects of High a-Olefins in Metallocene Catalyzed Terpolymerization: Thermal Properties - Kim, D.H. (Asian Journal of Chemistry, 2013)
A range of polymers were synthesized using a rac-Et(Ind)2ZrCl2 catalyst and methylaluminoxane co-catalyst system. The polymers, homo-, co- and terpolymers were comprised of ethylene, 1-decene and p-methyl styrene. The structures and compositions of the polymers were examined by 13C nuclear magnetic spectroscopy and 1H nuclear magnetic spectroscopy. The catalytic activity, weight-averaged molecular weight, number-averaged molecular weight and molecular weight distribution of the polymers were characterized. The glass transition temperature, melting temperature, crystallization temperature, crystallinity, storage modulus, loss modulus and tan d of the terpolymers according to the 1-decene feed molar concentration were also examined.